PERAN BADMINTON WORLD FEDERATION (BWF) TERHADAP PERKEMBANGAN OLAHRAGA BULU TANGKIS INDONESIA DI DUNIA INTERNASIONAL PERIODE 2015-2018 - Raenaldy Warto Kusumo (2021)
This research aims to describe the role of the Badminton World Federation (BWF) as a non-governmental international organization, namely the world badminton federation in the development of badminton in Indonesia from 2015 to 2018. This research uses qualitative research methods and is supported by international organizational theory and the role of international organizations in examine the title of this research. In the 2015 to 2018 period, BWF has done many things that encourage the progress of badminton in Indonesia, including helping to organize the 2015 BWF World Championship in Jakarta, organizing the 2017 BWF Junior World Championship in Yogyakarta and then a shuttle time program, namely education for elementary school children. in Indonesia regarding badminton until BWF succeeded in solving the scandal of Indonesian athletes who violated the BWF code of ethics in 2017. This was carried out by BWF in line with its role as an international organization in the field of badminton. Indonesia is also a country that is known for its love of badminton, this is also driven by the various achievements achieved by Indonesian athletes in the world badminton arena, even badminton is the only sport to have won a gold medal for Indonesia from the 1992 Barcelona Olympics to the Rio de janeiro Olympics 2016.